Exploring the Relationship Between Lifestyle Behaviors and Health-Related Quality of Life Among Older Adults With Diabetes. Issue 1 (February 2019) - Qin, Weidi; Blanchette, Julia E.; Murrock, Carolyn
Purpose: The purpose of the study was to examine the association between 3 lifestyle behaviors (smoking, physical activity, and fruit and vegetable consumption) and health-related quality of life (HRQOL) among older adults diagnosed with diabetes. Methods: A sample of the US population 65 years and older who were diagnosed with diabetes from the 2015 Behavioral Risk factor Surveillance System (N = 11 503) was analyzed. The 4 HRQOL measures were self-rated health, physically unhealthy days, mentally unhealthy days, and impaired activity days in the past month. Multiple logistic regression analysis was conducted to predict HRQOL. Results: The multiple logistic regression results showed that smoking and lack of physical activity were significant predictors for higher odds of fair or poor self-rated health, more physically unhealthy days, more mentally unhealthy days, and more impaired activity days during past 30 days. No significant relationship was found between fruit and vegetable consumption and any HRQOL measure. Conclusions: Findings imply that diabetes education could continue and enhance efforts in smoking cessation and increase physical activity to promote the HRQOL among older adults diagnosed with diabetes. In addition, the measure of fruit and vegetable consumption should be further studied to reflect the needs of older adults with diabetes.